(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of depression, anxiety, and stress using the DASS-21 scale among patients with OSA at the University Medical Center, Ho Chi Minh City. Materials and Methods: A descriptive cross-sectional study was conducted to determine the prevalence of depression, anxiety, and stress, as assessed by the DASS-21 questionnaire, in the obstructive sleep apnea population at University Medical Center HCMC. Results: The proportion of male participants was 78.2%. The mean age of participants was 51.51 ± 16.41 years. The mean body mass index (BMI) was 26.85 ± 5.30 kg/m². The median apnea-hypopnea index (AHI) was 38.71 (18.70–54.40). Based on AHI, the severity of obstructive sleep apnea was classified as mild in 21.8% of patients, moderate in 19.8%, and severe in 58.4%. The prevalence rates of depression, anxiety, and stress were 32.7%, 64.4%, and 30.7%, respectively. No statistically significant correlations were found between DASS-21 scores and age, sex, or AHI severity. Retired individuals had significantly higher depression and anxiety scores compared to those in intellectual occupations. Participants who had not completed lower secondary education had significantly higher anxiety scores than those who had graduated. Conclusion: Depression, anxiety, and stress are prevalent in OSA patients, especially anxiety. Socioeconomic factors such as occupation and education are associated with mental health status. Psychological screening and support should be integrated into OSA patient management.